APPLICABILITY OF SOME CALCINED CLAY AND CALCIUM CARBIDE WASTE IN CEMENT MIXES FOR DEVELOPMENT OF POZZOLANIC BINDER (Nigerian Journal of Technology, 2025)
This paper presents findings of an investigation on the applicability of Imotoyewa (IM), Ifonyintedo (IF), and Owode-Ketu (OK) clay from Nigeria, and calcium carbide waste (CCW) as a partial substitute for Ordinary Portland Cement (OPC) in the development of a pozzolanic binder. The CEM II was partially replaced with calcined Ifonyintedo clay (C-IF), calcined Owode-ketu clay (C-OK), and calcined Imotoyewa clay (C-IM) at intervals of 10% up to 50% and CCW was also used to replace C-IM, C-IF, and C-OK and at the same interval in a separate mix. Physicochemical, mineralogical, microstructural, Zeta-sizer analysis, Brunauer–Emmett–Teller (BET) methods, were used for characterization. The Index Strength index (SAI) of the burnt clay (CC), setting times of CEMII-CC, CC-CCW, and compressive strength by partially replacing cement with CC and whole cement replacement using CC with CCW were investigated. Results from the SAI indicated a high pozzolanic effect. C-IF with about 40% kaolinite content gave the highest mortar strength than the control at a substitution level of 20%. Kaolinite on the XRD trace was 34-40wt% in the clays, consistent with BET values. The BET and porosity of the CC were well above OPC while C-IF clay, with the highest kaolin content, had the highest limit. ST tests revealed that in the CEMII-CC and CC-CCW paste; CC and CCW inclusion have a linear relationship with the ST and water content of the paste owing to the pozzolanic reaction and dilution impact. They inhibit cement hydration; thus, their ability to retard could be useful with concrete in hot weather. The C-IF’s reactivity with Ca(OH)2 from CCW and CEM:CIC mortar showed similar and noticeable trends on the FTIR. Results have demonstrated the development of pozzolanic binders from blended cement mortar; calcined clay and CCW mortar.